First molecular records of bacteria infecting bagworms in oil palm plantations of South Sumatra, Indonesia - ERISE ANGGRAINI; EVI RIZKYANI NASUTION; SITI HERLINDA; CHANDRA IRSAN; AHMAD MUSLIM; SUWANDI SUWANDI; NURHAYATI DAMIRI; WEI HONG LAU (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Anggraini E, Nasution ER, Herlinda S, Irsan C, Muslim A, Suwandi S, Damiri N, Lau WH. 2026. First molecular records of bacteria infecting bagworms in oil palm plantations of South Sumatra, Indonesia. Biodiversitas 26 (1): d270118. https://doi.org/10.13057/biodiv/d270118. Bagworms such as Metisa plana, Pteroma pendula, and Mahasena corbetti are major defoliating pests in oil palm ecosystems and can cause substantial yield losses during outbreaks. Despite their economic importance, information on bacteria infecting these bagworm species in Indonesia remains limited. This study presents the first molecular identification of bacterial isolates obtained from three dominant bagworm species collected in Banyuasin, South Sumatra, Indonesia. Partial 16S rRNA gene sequences were analyzed using BLASTn and Bayesian phylogenetic inference to determine their taxonomic affiliations. The isolate from P. pendula was identified as Stenotrophomonas maltophilia, forming a well-supported clade with reference sequences in the Bayesian phylogenetic tree. The isolate from M. plana showed high sequence similarity to Bacillus thuringiensis, while the isolate from M. corbetti was identified as Mammaliicoccus sciuri and clustered distinctly from Staphylococcus species. All sequences were deposited in GenBank under accession numbers PX487709.1, PX487712.1, and PX487708.1, respectively. These findings represent the first molecular records of bacteria infecting oil palm bagworms in South Sumatra and demonstrate that different bagworm species can be infected by distinct bacterial taxa. A laboratory bioassay using third-instar Spodoptera litura larvae was conducted as a preliminary assessment of biological activity, indicating variable larval responses among the bacterial isolates. While B. thuringiensis remains the only well-established entomopathogenic species, the responses observed for S. maltophilia and M. sciuri suggest that their interactions with insect hosts merit further investigation. Overall, this study provides baseline molecular evidence of bacterial infections in oil palm bagworms and contributes to a broader understanding of insect-microbe diversity in plantation ecosystems.